1985
DOI: 10.1111/j.1365-3059.1985.tb02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Components of partial resistance to Puccinia striiformis in barley

Abstract: Substantial differences in the rates of mycelial growth and sporulation of different isolates of Puccinia striiformis were observed when seedling and upper leaves of five barley cultivars with susceptible reaction types were inoculated. The highest rate of mycelial growth was usually on cv. Sultan, followed by Proctor, Astrix, Senta and Zephyr in that order, but more spores were produced on Senta and Astrix than on Proctor, Zephyr or seedlings of Sultan. Host-specific differences between isolates were slight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
3
6
0
1
Order By: Relevance
“…In the seedling stage the differences in LP among cultivars were small. Osman-Ghani and Manners (1985), working with the same pathosystem, found similar results for winter barley. In the barley-barley leaf rust pathosystem Parlevliet (1975) and Parlevliet and Van Ommeren (1975) also observed small cultivar differences in LP in the seedling stage, while the LP in the flag leaf showed much larger differences between cultivars.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the seedling stage the differences in LP among cultivars were small. Osman-Ghani and Manners (1985), working with the same pathosystem, found similar results for winter barley. In the barley-barley leaf rust pathosystem Parlevliet (1975) and Parlevliet and Van Ommeren (1975) also observed small cultivar differences in LP in the seedling stage, while the LP in the flag leaf showed much larger differences between cultivars.…”
Section: Discussionsupporting
confidence: 70%
“…In both spring and winter barley it has been found that some cultivars have high infection types in the seedling stage associated with high levels of quantitative resistance in the adult plant stage (Osman-Ghani and Manners 1985;Sandoval-Islas et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Our results differ in that more variation is associated between incubation period, latent period, sporulation, and necrosis among genotypes when tested as seedlings than as adult plants in the field . Osman- Ghani & Manners (1985) reported similar findings for latent period and sporulation among barley genotypes compared for resistance to Puccinia striiformis . This may explain some of the differences between our results and those of Jeger et al .…”
Section: Discussionsupporting
confidence: 69%
“…Dierences in the degree of virulence of dierent isolates were also found by Osman- Ghani and Manners (1985).…”
Section: Resistance Testsmentioning
confidence: 61%